Análise da conformabilidade do aço ferrita bainita, comparativamente aos aços dual phase e microligado das classes de 600 MPa de limite de resistência - Petrus Barros Barcelos (2019)
The advanced high strength steel family (AHSS) continues to evolve and grow in application, especially in the automotive industry. New types of steel are already being used to improve the performance of vehicles on the roads, and these emerging steels will be increasingly used. Currently, two steel groups already have a long history of successful production and are widely used in the automotive industry: the Dual Phase (DP) steel and Titanium and Niobium (HSLA) microalloyed steels. At the same time, the Bainitic Ferrite (FB) steels have been gaining space in the structure of an automobile mainly in parts that require efforts such as edge stretching (flanging) and high hole expansion. This study aims to perform an analysis of the formability of a Bainitic Ferrite steel of the class 600 MPa of strength and compare it with the steels of the classes Dual Phase and HSLA also of 600 MPa of strength. The steps followed in this work were: producing the coils, obtaining samples and carrying out the following tests: tension, BH Effect, Age Index, Metalographic Analysis, MEV and MO, Erichsen Stretch, Limit Drawing Ratio (Swift Method), Conical Hole Expansion Test and CLC (Conformation Limit Curve). The results of the tests showed that the DP600 steel presented better performance in biaxial stretch deformation mode, at the same time, the FB580 and HSLA550 steels presented the same performance in the deep drawing deformation mode and it was the DP600 steel that presented the major ε1 major deformation in the CLC. FB580 steel presents better performance in the deformation mode by edge and flange stretching, which is the main advantage of this steel compared to the other two evaluated, which makes it more suitable for the manufacture of parts in which the operations of flanging are more severe.